Lipid rafts: linking prion protein to zinc transport and amyloid-β toxicity in Alzheimer's disease - Watt, Nicole T.; Griffiths, Heledd H.; Hooper, Nigel M. (Frontiers in Cell and Developmental Biology, 2014)
Dysregulation of neuronal zinc homeostasis plays a major role in many processes related to brain ageing and neurodegenerative diseases, including Alzheimer’s disease (AD). Yet, despite the critical role of zinc in neuronal function, the cellular mechanisms underpinning its homeostatic control are far from clear. We reported that the cellular prion protein (PrPC) is involved in the uptake of zinc into neurons. This PrPC-mediated zinc influx required the metal-binding octapeptide repeats in PrPC and the presence of the zinc permeable AMPA channel with which PrPC directly interacted. Together with the observation that PrPC is evolutionarily related to the ZIP family of zinc transporters, these studies indicate that PrPC plays a key role in neuronal zinc homeostasis. Therefore, PrPC could contribute to cognitive health and protect against age-related zinc dyshomeostasis but PrPC has also been identified as a receptor for amyloid-beta oligomers which accumulate in the brains of those with AD. We propose that the different roles that PrPC has are due to its interaction with different ligands and/or co-receptors in lipid raft-based signalling/transport complexes.